Structures internes claviculaires chez Pan, Gorilla et Homo. Méthode d’analyse et résultats préliminaires - Jean-Luc Voisin; Antoine Balzeau (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
This study presents the preliminary results of an examination of internal clavicular structures using CT scan data analysis. The complex morphology of this bone makes the determination of a reproducible CT slice plane impossible and so any classical analysis of the two-dimensional CT data is ruled out. We propose a new protocol which enables quantification in three dimensions of the variations in volume of the internal morphological structures of the clavicles.  These are divided into three distinct groups (porosity, low density structures and high density structures) according to their radiological density. The first results show that the high density structures are represented by a larger volume than the low density structures. Moreover, chimpanzee clavicles are characterized by a relative volume of high density bone structure superior to that of gorillas and humans. For a quarter of chimpanzees, this is characterized by an absence of low density structures at the inflexion point of the acromial curvature. These differences can be interpreted as adaptations to the strains to which the clavicles are subjected.